From the Village to the World: Strengthening the Economic Independence of the Sewagati Women's Working Group through Partnership with the Merah Putih Cooperative - Hajarana Hajarana; Asyri Lapodo; Luciana Anggriani Abigeil Langkamau; Anastasia Reti Werang; Endang Sri Utami; Loo Wen Hui; Prashanth Beleya (Universitas 45 Surabaya, 2026)
The Sewagati Women Farmers Group (KWT) in Balecatur Village, Gamping, Sleman, Yogyakarta has great potential in developing organic farming, processing crops, and managing waste banks. However, this group faces various challenges such as limited business capital, weak managerial and administrative capacity, minimal understanding of the cooperative system, and limited access to product marketing. This International Community Service Program (KKN) aims to build a strategic partnership between KWT Sewagati and the Merah Putih Cooperative to promote the independence and economic welfare of members, as well as to develop sustainable marketing strategies. The implementation method uses a participatory approach through location surveys, in-depth interviews, and partnership socialization. The results of the activities showed an increase in members' understanding of the benefits of cooperatives in terms of access to capital, marketing networks, and strengthening the people's economy. Input from Malaysian partners emphasized the importance of operational digitization, contract farming models, product certification, sustainable agricultural practices, and women's leadership training. This program is expected to become a transformative model for empowering women farmers, turning the potential of villages into global market opportunities through synergy between community groups, cooperatives, universities, and the government in realizing inclusive and sustainable economic development.